A single centre's experience of caesarean scar pregnancy and proposal of a management algorithm. (17th February 2019) - Tahaoglu, Ali Emre; Dogan, Yasemin; Bakir, Mehmet Sait; Baglı, Ihsan; Peker, Nurullah; Cavus, Yunus; Togrul, Cihan; Tahaoglu, Zelal
Abstract: The management of a caesarean scar pregnancy ranges from conservative medical therapy to surgical treatment. The aim of this study is to present our experience of caesarean scar ectopic pregnancies treated with different modalities and to develop a management algorithm. This retrospective clinical analysis included 21 caesarean scar pregnancies. The clinical data, ultrasonographic characteristics, b-human chorionic gonadotropin concentrations, the treatment options and complications were noted. One patient was managed expectantly, six patients were treated with D and C, seven patients were treated with systemic methotrexate, eight patients underwent a caesarean scar pregnancy removal with a laparoscopy, three patients were treated with a hysteroscopy. Three patients who recieved a methotrexate required additional treatment methods including a laparoscopy, hysteroscopy and D and C. Surgery was successful in all cases. An intra-abdominal haemorrhage from the vessels in the scar area occured in the patient managed expectantly, and a laparatomy and removal was performed. A systemic methotrexate, dilatation and curettage, hysteroscopic resection and laparoscopic resection are feasible methods for scar pregnancy treatment depending on the gestational age, β-hCG level, the type of scar pregnancy and the clinical status of the patient. IMPACT STATEMENT: What is already known on this subject? CSP has increased gradually parallel to the increased rates of CS worldwide. There is no treatment consensus on that rare entity. What do the results of this study add? We aimed to present our cases and to discuss a proposal algorithm with further studies. What are the implications of these findings for clinical practice and/or further research? Our cases and proposal algorithm could help to determine the treatment options for CSP.